2023
DOI: 10.3390/ijms241813819
|View full text |Cite
|
Sign up to set email alerts
|

New Copper Complexes with Antibacterial and Cytotoxic Activity

Adriana Corina Hangan,
Roxana Liana Lucaciu,
Alexandru Turza
et al.

Abstract: The discovery of a new non-toxic metal complex with biological activity represents a very active area of research. Two Cu+2 complexes, [Cu4(L1)4(OH)4(DMF)2(H2O)] (C1) (HL1 = N-(5-ethyl-[1,3,4]–thiadiazole–2-yl)-benzenesulfonamide) and [Cu(L2)2(phen)(H2O)] (C2) (HL2 = N-(5-(4-methylphenyl)-[1,3,4]–thiadiazole–2-yl)-naphtalenesulfonamide), with two new ligands were synthesized. The X-ray crystal structures of the complexes were determined. In both complexes, Cu+2 is five-coordinated, forming a CuN2O3 and CuN4O c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The existence of phenyl and pyrazole groups within the pyrazole‐based ligand (Figure 1) is critical for evaluating the antitumor activities and the ability to interact with DNA. The aromatic structures within the ligand allow the complex to be close and interact with base pairs of the DNA via π‐stacking bonding 6 . Further studies are required to investigate the mode of action.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of phenyl and pyrazole groups within the pyrazole‐based ligand (Figure 1) is critical for evaluating the antitumor activities and the ability to interact with DNA. The aromatic structures within the ligand allow the complex to be close and interact with base pairs of the DNA via π‐stacking bonding 6 . Further studies are required to investigate the mode of action.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cells exhibit reduced vascularity causing a low level of O 2 , leading to the anaerobic process called the Warburg effect. The absence of O 2 within the cancer cell could allow the reduction of copper from the divalent to monovalent state giving an opportunity to copper compounds to target tumor cells 6 …”
Section: Introductionmentioning
confidence: 99%
“…Anal. calculated for ZnC 30 A solution of the ligand (0.1267 g, 0.5 mmol) and ZnCl 2 (0.0341 g, 0.25 mmol) in 15 mL of ethanol was stirred under reflux for 30 min. The reaction mixture was left to stand at room temperature.…”
Section: [Ni(seabz) 2 Br 2 ] (4)mentioning
confidence: 99%
“…In the presence of a reducing agent, these compounds induce DNA damage by ROS generation. Cytotoxicity studies with different cancer cell lines revealed that complexes [Cu(tnz) 2 (µ-Cl)Cl] 2 and [Cu(tnz) 2 Br 2 ] showed the highest cytotoxicity, while being moderately toxic to normal cells [26,27] Generally, the reported cytotoxic transition metal compounds have been synthesized using chelating ligands [28][29][30][31][32][33][34]. The results with non-chelating ligands, tinidazole and clotrimazole [35][36][37][38][39][40][41][42], have shown that weak interactions, such as hydrogen bonding, electrostatic interactions, π stacking, lp•••π or hydrophobic contacts, as well as geometry and redox properties, have an important role in the biological activity of coordination compounds with monocoordinated ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a reducing agent, these compounds induce DNA damage by ROS generation. Cytotoxicity studies with different cancer cell lines revealed that complexes [Cu(tnz) 2 (µ-Cl)Cl] 2 and [Cu(tnz) 2 Br 2 ] showed the highest cytotoxicity, while being moderately toxic to normal cells [26,27] Generally, the reported cytotoxic transition metal compounds have been synthesized using chelating ligands [28][29][30][31][32][33][34]. The results with non-chelating ligands, tinidazole and clotrimazole [35][36][37][38][39][40][41][42], have shown that weak interactions, such as hydrogen bonding, electrostatic interactions, π stacking, lp•••π or hydrophobic contacts, as well as geometry and redox properties, have an important role in the biological activity of coordination compounds with monocoordinated ligands.…”
Section: Introductionmentioning
confidence: 99%